Evaluation Study on National Project on Biogas Development - Planning Commission (Planning Commission, 2002)
The origin of the National Project on Biogas Development, launched in 1981-82 by the Ministry of Non - Conventional Energy Sources, can be traced back to 1970s when successive oil crises and their fallout effect on economic growth necessitated development of alternative sources of energy. Though the socio-economic and environmental impact of biogas is well recognized, NPBD has been receiving public attention and scrutiny in India because of its vast potential on the one hand and its poor performance, high mortality and non functionality rates on the other. At the instance of MNES, the Programme Evaluation Organization (PEO) undertook evaluation of NPBD primarily to examine if the implementation methods being currently followed are contributing to increased adoption of family type plants and to reduced mortality and non functionality rates. The study is also designed to identify the factors contributing to success and failure, to examine the efficacy of family type biogas plants as an instrument to realize the biogas potential and to reflect on alternate strategies for biogas development.
Programme Evaluation Organisation Planning Commission Government of India New Delhi